Gambaran Efektivitas Terapi Kombinasi Antidiabetik terhadap Nilai HbA1c pada Pasien Rawat Jalan Diabetes Mellitus Tipe II di Rumah Sakit Anna Pekayon Periode Agustus 2022 – Januari 2023: Overview of the Effectiveness of Combination Antidiabetic Therapy on HbA1c Levels in Type 2 Diabetes Mellitus Outpatients at Anna Hospital Pekayon for the Period of August 2022 – January 2023 - Cory Imawati; Ariyanti Kusumadewi; Risti Arista (UIMA Press, 2024)
Diabetes mellitus is still a health problem of concern. Antidiabetic pharmacotherapy can be carried out using one type or a combination of 2 types of drugs. This scientific work aims to describe the effectiveness of a combination of antidiabetic therapy on HbA1c values in type 2 diabetes mellitus outpatients at Anna Pekayon Hospital. The research method uses univariate analysis to obtain an overview of the effectiveness of a combination of antidiabetic therapy on HbA1c values. Data collection was conducted from August 2022 to January 2023, involving a sample of 90 respondents. The independent variables are age, gender, diagnosis, and diabetes mellitus treatment, and the dependent variable is the HbA1c value. The data taken was then processed using SPSS to determine the frequency distribution of each variable. The results of data processing showed that most combinations used ado therapy with ado, with the number of prescriptions being 47 (52.2%), compared to the combination of ado with insulin, with the number 25 (27.8%), and the combination of insulin with insulin, 18 (20.0%). The most widely used combination of ADO and ADO therapy was the combination of Metformin with glimepiride in 29 patients (61.7%). The effectiveness of the combination of antidiabetic therapy with antidiabetic therapy on the HbA1c value was highest in the combination of 2 ados with a total of 21 patients. This can be because respondents found non-compliance in the use of insulin due to a lack of education, or characteristics of people with diabetes mellitus, such as age, which can affect their understanding of insulin use. In contrast to oral use, which is easier and more practical to use that it allows more effective control of HbA1C.